Relationship between Body Mass Index and Bone Turnover Markers in Girls with Idiopathic Central Precocious Puberty - Jing Zhang; Wen-jie Zhou; Yi-duo Zhang; Chuan-jiao Liu; Fan Yu; Yong-mei Jiang (International Journal of Clinical Practice)
Background. This study aimed to determine the effect of body mass index (BMI) on bone turnover markers in girls with idiopathic central precocious puberty (ICPP) according to weight status at diagnosis. Methods. Two hundred and eleven girls with ICPP were divided according to their weight status at diagnosis into three groups: normal weight, overweight, and obese. The serum levels of total procollagen type 1 N-terminal propeptide (P1NP), N-terminal midfragment of osteocalcin, β-C-terminal telopeptide of type 1 collagen, and some biochemical indicators were measured. Associations between variables were evaluated by multiple regression analysis. Results. Serum P1NP concentrations were significantly different among groups (p<0.001). No other significant differences were noted in N-terminal midfragment of osteocalcin and β-C-terminal telopeptide of type 1 collagen. BMI was associated with estradiol (r = 0.155, p<0.05) and inversely associated with P1NP (r = −0.251, p<0.01), luteinizing hormone peak (r = −0.334, p<0.01), follicle-stimulating hormone peak (r = −0.215, p<0.01), and luteinizing hormone/follicle-stimulating hormone peak (r = −0.284, p<0.01). Multiple regression analysis of factors associated with BMI showed that it was correlated with P1NP, follicle-stimulating hormone base, and luteinizing hormone peak in the overweight group and the obese group. Conclusions. Our findings showed that BMI was associated with P1NP, revealing the reduction of bone formation in overweight and obese girls with ICPP. During the diagnosis and treatment of girls with ICPP, attention should be paid to body weight and bone metabolism.